Heartstopper. Volume 1 - Oseman, Alice (Heartstopper, 2020)
"Boy meets boy. Boys become friends. Boys fall in love. Shy and softhearted Charlie Spring sits next to rugby player Nick Nelson in class one morning. A warm and intimate friendship follows, and that soon develops into something more for Charlie, who doesn't think he has a chance. But Nick is struggling with feelings of his own, and as the two grow closer and take on the ups and downs of high school, they come to understand the surprising and delightful ways in which love works."--Page 4 of cover.